2024
DOI: 10.1038/s41598-024-60249-6
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical identification of acute coronary syndrome without high sensitivity troponin assays using machine learning algorithms

Andreas Goldschmied,
Manuel Sigle,
Wenke Faller
et al.

Abstract: Preclinical management of patients with acute chest pain and their identification as candidates for urgent coronary revascularization without the use of high sensitivity troponin essays remains a critical challenge in emergency medicine. We enrolled 2760 patients (average age 70 years, 58.6% male) with chest pain and suspected ACS, who were admitted to the Emergency Department of the University Hospital Tübingen, Germany, between August 2016 and October 2020. Using 26 features, eight Machine learning models (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…For instance, Rashed-Al-Mahfu et al [30] successfully demonstrated the effectiveness of SHAP value analysis in identifying key frequency features that impact ECG signal classification. Moreover, Goldschmied et al [31] used SHAP value analysis to reveal ST-segment elevation in ECG as a key predictor of cardiac events, while Mehari et al [32] showed a strong correlation between SHAP values and other feature importance ranking methods, providing new perspectives for heart disease diagnosis. The ECG-iCOVIDNet model proposed by Agrawal et al [33] enhanced the interpretability of ECG changes in COVID-19 convalescent patients using SHAP technology, and Jekova et al [34] assessed the importance of atrioventricular synchrony in atrial fibrillation detection with SHAP value analysis.…”
Section: Comparison With Existing Workmentioning
confidence: 99%
“…For instance, Rashed-Al-Mahfu et al [30] successfully demonstrated the effectiveness of SHAP value analysis in identifying key frequency features that impact ECG signal classification. Moreover, Goldschmied et al [31] used SHAP value analysis to reveal ST-segment elevation in ECG as a key predictor of cardiac events, while Mehari et al [32] showed a strong correlation between SHAP values and other feature importance ranking methods, providing new perspectives for heart disease diagnosis. The ECG-iCOVIDNet model proposed by Agrawal et al [33] enhanced the interpretability of ECG changes in COVID-19 convalescent patients using SHAP technology, and Jekova et al [34] assessed the importance of atrioventricular synchrony in atrial fibrillation detection with SHAP value analysis.…”
Section: Comparison With Existing Workmentioning
confidence: 99%